Effect of process parameters on the laser microdrilling performance of stainless steel, aluminium and copper - Noor, Wazed Ibne; Saleh, Tanveer; Rashid, Mir Akmam Noor; Ibrahim, Azhar Mohd (2021)
Micromachining techniques are being used regularly in various engineering and production sectors such as Micro Electromechanical Systems, Aerospace, Automotive, Electronics and Biomedical industries. For Laser Beam Micromachining, highly energized laser beam is focused on a small region of the workpiece surface. As a result, it is heated up rapidly to sufficiently high temperatures, then the material starts to melt and/or vaporize from the surface. This phenomenon of material removal is called laser ablation. The holes that are produced by one-dimensional laser beam drilling (LBD) can come with defects like taper, heat affected zone (HAZ) and Recast Layer. On the other hand, LBD process offers high control, high efficiency, precision, and production rate, particularly for drilling microscopic holes in a variety of materials. LBD performance is measured on different parameters such as taper and recast layer of the machined holes. Previous studies report many observations regarding the performance parameters and the process input parameters. But a thorough study of the performance parameters with respect to different material properties has not been reported yet. The research work for this paper focuses on the experimental investigation for different materials such as stainless steel (type SS304), Aluminum and Copper to observe the effects of Laser input parameters (namely laser power, scanning speed, and pulse repetition rate) on the performance of the LBD. The study also considers different thermophysical as well as optical properties such as thermal conductivity, specific heat, melting point, absorptivity and how it affects the outcome of LBD in a combined manner. Characterization of different output parameters such as Entry area, Exit Area and Recast Area is done by SEM (Scanning Electron Microscope) machine. For 75 Loop count, 90% Laser Power, 950 mm/s Scanning Speed and 10kHz pulse repetition rate, the highest amount of Recast Area is observed in SS, valued at 0.053 mm2. The largest amount of taperness is found in Cu at 44.404º. Scanning Speed and Laser Power has been identified as the most significant process factors for LBD performance.